AFFECTIONS, EXERCISES, THEATER PROTOPEDAGOGIES (Revista Rascunhos - Caminhos da Pesquisa em Artes Cênicas, 2023)
Reflective exposition on exercises and criteria for conducting pedagogical theaterprocesses based on concepts from the works of Gilles Deleuze and Félix Guattari.The text discusses specificities of perspective and pedagogical approaches that suchconcepts propose for the body, the performer and the conductor of the processes,particularly in contemporary issues related to the imbrication between art and life -an aesthetic education concerning the theatrical scope of life.